Prenatal Ultrasound Signs of Cornelia de Lange Syndrome in Monochorionic Twins: Case Study - Nodira M. Normuradova; Odil A. Khujakulov; Mahliyo Sh. Ergasheva; Eshdavlat R. Ollanazarov; Bekhruz B. Majidov (Вопросы современной педиатрии)
Background. Cornelia de Lange syndrome is rare genetic disease manifested by short stature, limb abnormalities, craniofacial dysmorphies, and developmental delay. Syndrome prenatal detection is crucial during ultrasound diagnosis.Clinical case description. Growth delay of both children (body weight indicators were less than the 1st percentile) without any pathological changes in utero-fetoplacental perfusion (according to Doppler) was revealed during the ultrasound examination of monochorial twins in the II trimester of pregnancy. Hydramnious was noted. Fetal echocardiography has revealed transposition of main arteries in the first intrauterine child. Examination of fetus facial structures has shown nose bridge depression, upturned nose, elongated filter, and micrognathy. Second child has shown features of heterotypic abnormalities of upper limbs. One forearm bone was missing on the left side, presumably ulnar, the radial bone was shortened, and there was oligodactyly (only 2 fingers were visualized). There was no digitus annularis on the right hand, and there was clinodactyly of the fifth finger. Genetic testing was not performed due to the inaccessibility of this method in the country of residence and the financial limitations of the family to perform it elsewhere. Male twins were born prematurely on 35th week of pregnancy with weight of 1680 and 1640 (body weight indicators were less than the 5th percentile). Babies were consulted by the geneticist after birth, clinical diagnosis of Cornelia de Lange syndrome was established. The child with heart defect died on the 23rd day of his life, the second was discharged in satisfactory condition.Conclusion. Cornelia de Lange syndrome may manifest in monochorionic twins. The diagnosis of intrauterine growth delay in the II-III trimesters of pregnancy, without impaired uterofeto-placental perfusion, especially associated with hydramnious, requires searching for structural abnormalities and examination of facial dysmorphies specific for chromosomal or genetic diseases.